Investigation of Power Levels Related to Different EMF Exposure Metrics at 6 GHz - Walid El Hajj; John Roman; Zhen Yao; Robert Paxman; Valerio De Santis (IEEE Access, 2023)
New wireless technologies significantly utilize the spectrum around 6 GHz with some of them, like Wi-Fi®6E, using both the spectrum below and above 6 GHz. At these frequencies, the main challenge for electromagnetic field (EMF) exposure assessments is due to the exposure metric changing from specific absorption rate (SAR) to absorbed power density (APD). Moreover, due to current measurement limitations, the incident power density (IPD) rather than APD is used in practice. In this context, the maximum allowed output power to ensure exposure compliance is dependent on the metric used and can lead to a discontinuity below and above 6 GHz even for different channels of the same technology. This paper studies such a discontinuity at the transition frequency of 6 GHz using a dipole antenna and a Planar Inverted F Antenna (PIFA). The study was performed at several exposure distances by means of numerical simulations as well as experimental measurements. The assessment was based on the comparison between maximum power values obtained while remaining compliant to the SAR and IPD limits for the same exposure conditions. The results have shown that for a specific source there was a distance (between 5 and 10 mm) where the highest power reduction for compliance switched from SAR to IPD. The difference or discontinuity level varied between 2 and 6 dB depending on the exposure distance and the source. In summary, SAR is more restrictive at closer distances, while the IPD induces a higher back-off power with an increase in distance.